Financial intermediation and the role of price discrimination in a two-tier market - Stefan Reitz; Markus A. Schmidt; Mark P. Taylor (Kiel Institute for the World Economy (IfW), 2012)
Though unambiguously outperforming all other financial markets in terms of liquidity, foreign exchange trading is still performed in opaque and decentralized markets. In particular, the two-tier market structure consisting of a customer segment and an interdealer segment to which only market makers have access gives rise to the possibility of price discrimination. We provide a theoretical foreign exchange pricing model that accounts for market power considerations and analyze a database of the trades of a German market maker and his cross section of end-user customers. We find that the market maker generally exerts low bargaining power vis-á-vis his customers. The dealer earns lower average spreads on trades with financial customers than commercial customers, even though the former are perceived to convey exchange-rate-relevant information. From this perspective, it appears that market makers provide interdealer market liquidity to end-user customers with cross-sectionally differing spreads.
Keywords: F31; 330; foreign exchange; market microstructure; pricing behavior